Aktivitas Hepatoprotektif Ekstrak Daun Sukun (Artocarpus altilis (Park.) Fsb.) pada Mencit Balb/C yang Diinduksi Vaksin Hepatitis B - TRI WIJAYANTI; VIVIN NOPIYANTI; IKA PURWIDYANINGRUM (Jurnal Farmasi Indonesia, 2013)
Breadfruit leaves (Artocarpus altilis (Park.) Fsb.) is a medicinal plant that is thought to have potential as a hepatoprotective. In the community itself has been widely used and is reported to have many uses since it contains efficacious compounds in plants such as saponins, polyphenols, tannins, hydrocyanic acid, acetylcholine, riboflavin and flavonoids. This study aimed to determine the hepatoprotective effect of breadfruit leaves extract in mice induced by hepatitis B vaccine with the percentage of liver cell necrosis as parameter. Breadfruit leaves extract was made by percolation method with ethanol 70% as the solvent. The animal test was induced by hepatitis B vaccine, then they was grouped into 5 groups of negative control group were given CMC 1%, the positive control group were given Echinacea (Imboost®) and the treatment group of test animals were given breadfruit leaf extract at a dose 750 mg/kgBW, 1200 mg/kgBW, 1650 mg/kgBW. Hepatoprotective effect was observed by liver necrosis parameter on histopathologic liver mice preparations at day 35 after treatment. The results showed that the breadfruit leaf extract can provide hepatoprotective effect by reduction the liver necrosis. The percentage of reduction necrosis of the liver in the treatment of 70% ethanol extract of breadfruit leaves dose of 1200 mg/kgBW provides the most effective hepatoprotective effect on male mice induced hepatitis B vaccine.